2019
DOI: 10.1007/978-3-030-04849-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Distributed Marketplace

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…Blockchain is a sequence of blocks that holds the complete record of transactions [14] verified and validated by peer-to-peer nodes in network without using any central authority [15]. Recent Innovations in Blockchain technology have enabled the creation of smart contracts that automatically stores and executes code on the blockchain [16]. It also deals with the transferring of ether cryptocurrency in digital wallets without involving any trusted third party [17].…”
Section: Figure 1 Agile Software Development Lifecyclementioning
confidence: 99%
“…Blockchain is a sequence of blocks that holds the complete record of transactions [14] verified and validated by peer-to-peer nodes in network without using any central authority [15]. Recent Innovations in Blockchain technology have enabled the creation of smart contracts that automatically stores and executes code on the blockchain [16]. It also deals with the transferring of ether cryptocurrency in digital wallets without involving any trusted third party [17].…”
Section: Figure 1 Agile Software Development Lifecyclementioning
confidence: 99%
“…An example of a distributed marketplace was proposed in [261], where a marketplace contract lists the products and an escrow agent contract serves for resolution of disputes by a mediator (viz. single or group-based mediator).…”
Section: F Escrowsmentioning
confidence: 99%
“…Blockchain-based marketplaces are supposed to have several advantages and benefits. For a distributed online marketplace based on Ethereum, [131] showed that costs are less than that of Amazon or eBay for a large number of users. Blockchain-based marketplaces have already been proposed for different use-cases, like IoT data [132], software testing [133], or trading of agricultural products between farmers and other stakeholders [134].…”
Section: Open Research Regarding the Use-casesmentioning
confidence: 99%